Weighted Composition Operators and Supercyclicity Criterion - Bahmann Yousefi; Javad Izadi (International Journal of Mathematics and Mathematical Sciences)
We consider an equivalent condition to the property of Supercyclicity Criterion, and then we investigate this property for the adjoint of weighted composition operators acting on Hilbert spaces of analytic functions.